2009
DOI: 10.1007/s11552-009-9226-3
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study on the Initial Results of a Low Profile Ulna Shortening Osteotomy System

Abstract: Extra-articular ulna shortening osteotomy, in principle, is an accepted treatment option for symptomatic degenerative and traumatic triangular fibrocartilage complex (TFCC) tears. Despite the benefits of this surgical approach, potential disadvantages include risk of nonunion, soft tissue irritation, and the need for future hardware removal. A recently introduced low profile ulna shortening system was designed to decrease these potential complications. A single-surgeon prospective study was performed to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…45 Newer, low-profile plates and volar placement of the plate can greatly decrease the incidence of hardware removal. 46 Ulnar shortening osteotomy has few contraindications. Absolute contraindications include established DRUJ arthritis and dorsal DRUJ dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…45 Newer, low-profile plates and volar placement of the plate can greatly decrease the incidence of hardware removal. 46 Ulnar shortening osteotomy has few contraindications. Absolute contraindications include established DRUJ arthritis and dorsal DRUJ dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, PRWE scores are not better, nor worse than PWRE scores reported in other literature (scores ranging from 15 to 42). 6,24,29 Das et al reported no significant difference in PRWE when dorsal plating is compared with volar plating. 6 When a comparison is made between pre-and postoperative PRWE and DASH scores, a significant reduction of scores is seen.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest DASH score is reported at a follow-up of 11 years. 14,16,18,[24][25][26] After placement of hardware on the ulnar border, postoperative DASH scores range from 21.0 to 37.21. 19,27,28 No study reported on postoperative DASH scores after application of plates on the dorsal surface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations